Urban climate in urban design: how land use patterns and building types influence the urban comfort (1999)
This paper will argue the importance of consider urban climate in the urban spatial quality, improving urban comfort in the public spaces. The main topics taken into consideration were the land use patterns and the building types. The role of the architect here takes importance in the way to get a sustainable future.